1996
DOI: 10.1074/jbc.271.39.23623
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl Cyclase G, an Osmosensor Controlling Germination of Dictyostelium Spores

Abstract: Dictyostelium cells express a G-protein-coupled adenylyl cyclase, ACA, during aggregation and an atypical adenylyl cyclase, ACG, in mature spores. The ACG gene was disrupted by homologous recombination. acg- cells developed into normal fruiting bodies with viable spores, but spore germination was no longer inhibited by high osmolarity, a fairly universal constraint for spore and seed germination. ACG activity, measured in aca-/ACG cells, was strongly stimulated by high osmolarity with optimal stimulation occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 22 publications
1
96
0
Order By: Relevance
“…In these organisms, adenylate cyclase is considered to function as a receptor or a sensor (2,38). Recently, the adenylate cyclase of Dictyostelium that is expressed in spores was shown to be involved in sensing extracellular osmolarity (48). It is strongly suggested that the CyaA-like adenylate cyclase of cyanobacteria functions as a receptor or sensor.…”
Section: Discussionmentioning
confidence: 99%
“…In these organisms, adenylate cyclase is considered to function as a receptor or a sensor (2,38). Recently, the adenylate cyclase of Dictyostelium that is expressed in spores was shown to be involved in sensing extracellular osmolarity (48). It is strongly suggested that the CyaA-like adenylate cyclase of cyanobacteria functions as a receptor or sensor.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, ACG is localized on the spore surface, where it is directly activated by its extracellular osmo-sensing domain (Van Es et al, 1996). High levels of ammonium phosphate are released during spore maturation.…”
Section: Camp Regulation Of Fruiting Body Formationmentioning
confidence: 96%
“…In the 1990s, it became clear that, in addition to extracellular cAMP, intracellular cAMP acting on PKA was also required for prespore differentiation and was, furthermore, essential for spore and stalk maturation and for the control of spore germination (Harwood et al, 1992;Hopper et al, 1993;Van Es et al, 1996). For stalk and spore maturation, cAMP is produced by adenylate cyclase R (ACR), whereas cAMP for induction of prespore differentiation and control of spore germination is produced by adenylate cyclase G (ACG) Van Es et al, 1996;Alvarez-Curto et al, 2007). ACR harbours seven transmembrane domains and is embedded in the nuclear membrane of prestalk cells Alvarez-Curto et al, 2007;Chen et al, 2011).…”
Section: Camp Regulation Of Fruiting Body Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the fruiting body, spores are kept dormant by high osmolality, which directly activates ACG. ACG then activates PKA, resulting in inhibition of spore germination (22). In cyst forming species, such as Ppal, encystation is triggered by high osmolality, a signal for approaching drought, and this response is also mediated by ACG acting on PKA (12).…”
Section: Sporulation and Encystation Share Common Signaling Requiremementioning
confidence: 99%